Os determinantes da duração do desemprego em São Paulo - Picchetti, Paulo (2000)
This paper examines the determinants of unemployment duration in the metropolitan region of São Paulo in 1997. The descriptive statistics show that around 52% of the unemployment lived with their parents, that their average age was 27 and that 80% had between 4 and 11 years of schooling. Moreover, 85% of the 1997 unemployed left this status in the following three months, although on1y half of them effectively found a new job. The econometric results show that unemployment duration if lower for heads and for those that worked before. Moreover, duration is higher for the more educated, for those that lost their previous job, for the older and for those with longer tenure in the previous work. Finally, the hazard rate is increasing with the duration of unemployment up to the sixth month, dec1ining afterwards.